Christianity and the Detective Story. - Raubicheck, Walter (Cambridge Scholars Publishing, 2013)
Christianity and the Detective Story is the first book to gather together academic criticism on this particular connection between religion and popular culture. The articles cover the origin of this relationship in the works of G.K. Chesterton, examine its development through the ""Golden Age"" of mystery writers such as Dorothy L. Sayers, and include discussions of recent and contemporary television crime dramas. The volume makes a strong case for viewing mystery writing as a valid means of p ...